Recent advances in mechanical properties of biopolymer composites: a review - Sadasivuni, Kishor Kumar; Saha, Prosenjit; Adhikari, Jaideep; Deshmukh, Kalim; Ahamed, M. Basheer; Cabibihan, John‐John (Polymer composites, 2020)
In recent years, biopolymers are getting wide attention with the perspective of developing high‐performance biocomposites with low environmental impact owing to their unique and useful features such as abundant availability, renewability, eco‐friendliness and lightweight. Biopolymer composites are expected to replace many conventional materials in optical, biological, and engineering applications as the investment and research on these materials increase substantially. The desired properties of biopolymer composites can be achieved by blending an appropriate biopolymer with suitable additives, which pave the way for polymer‐filler interaction. A variety of parameters such as chemical composition, degradation kinetics and mechanical properties of biopolymer composites can be tailored according to the application needs. The interfacial interactions between the biopolymer and the nanofiller have a significant effect on the mechanical properties of biopolymer composites. The present review is focused on the recent advances in the mechanical properties of various biopolymer composites. In the first part of this review, the unfamiliar mechanical characterization techniques such as fatigue test, nanoindentation and nondestructive testing of biopolymer composites have been discussed. In the later part, the various popular processing techniques of biocomposite fabrication have been discussed. In addition, in the conclusion section, few challenges associated with the processing and mechanical performance of biopolymer composites have been described.